Peripheral nerve function in patients with chronic bronchitis receiving almitrine or placebo. - Allen, M B (1989)
A double blind prospective study of the effect of almitrine bismesylate and placebo on peripheral-nerve function was carried out in 12 patients with chronic bronchitis and arterial hypoxaemia (mean (SD) FEV1% predicted 38 (16), arterial oxygen tension (PaO2) 7.56 (0.76) kPa). Of the seven patients who took placebo, none developed symptoms or signs of peripheral neuropathy. One patient who had abnormal lower limb sensory nerve conduction initially showed improvement of sensory conduction but deterioration in motor conduction during the 12 month study period. Two further patients developed some slowing of motor conduction velocities in their right lateral popliteal nerve. Five patients received almitrine and all showed an improvement in PaO2 (mean from 7.0 to 7.9 kPa). None had symptoms or signs of peripheral neuropathy on entry to the study; one patient had evidence of impaired nerve conduction on electrophysiological testing. Three patients developed symptoms and signs of peripheral neuropathy during the 12 months of the study and a fourth developed peripheral neuropathy at 18 months, having continued to receive almitrine. Studies of nerve physiology showed abnormalities in the lower limbs of all four patients. Recovery was poor, possibly because of the long half life of almitrine. The studies suggest that almitrine may precipitate peripheral neuropathy in patients with chronic obstructive pulmonary disease. Patients should be warned of this potential complication so that the drug can be stopped as soon as symptoms develop.